Socio-demographic Determinants of Hypovitaminosis D (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hypovitaminosis D is a silent but very devastating health issue throughout the world. Socio-demographic factors have some role on the issue.Objectives: To determine the sociodemographic determinants of hypovitaminosis D among the clients attending specialized hospitals.Materials and Methods: This cross-sectional study was conducted among 264 respondents attended the Armed Forces Institute of Pathology, Dhaka Cantonment for estimation of 25(OH) D within the period of July 2017 to June 2018.Results: Respondentsmeanage was 48.23±14.05 years and themajority (68.56%) were female among themhalf (49.72%) were menopausal. All the clients were educated and majority (68.18%) had crossed the level of higher secondary. The mean ± SD of monthly family income was Taka 68824.46±23.92 and majority (57.57%) were from higher socioeconomic group. A large portion (47.35%) of the respondents was housewives followed by (26.56%) government employee. The mean± SD level of 25(OH) D of total population was 50.01±29.93 nmol/L butamong the male and female it was 50.86±28.61 nmo/L and 49.60±26.19 nmol/L respectively. Menopausal women (48.03±28.11 nmol/L) had significantly(p